PERANCANGAN MEDIA PRESENTASI COMPANY PROFILE UNIVERSITAS NEGERI PADANG BERBASIS MULTIMEDIA INTERAKTIF - Budiman Budiman; Muhammad Adri; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
Along the development of information technology today pose a tremendous impact for the community. Advances in information technology that has many benefits have not been utilized optimally in the process of delivering information. Today information technology has achieved various forms of multimedia presentation and ways of delivering information to the public in a dynamic and interesting in multimedia form as part of the development of information technology. This final project aims to develop media presentations Company Profile Padang State University-based interactive multimedia that can add insight to the public about the general picture Padang State University. The use of this interactive presentation media will be able to provide a better experience than other media because the media used when there are two senses that act simultaneously, namely the senses of sight and sense of hearing. For organizing or designing media interactive presentations of this, the development method used is the method of multimedia development ADDIE (Analysis, Design, Develop, Implementation and Evaluation) and designed using the software Adobe Flash CS6, Adobe Photoshop CC, Corel Draw X6, Voice Changer, Sony Vegas Studio and Flash Optimizer 2.1. The results of this interactive presentation media manufacture shaped Compact Disc (CD) that can be run on a computer device. After testing against media presentations interactive CD,s, it can be concluded that all test pages can run well and according to plan for each menu and submenu.Keywords:Company Profile,CDInteractive,MediaPresentation, ADDIE.